Blister formation in ZrN/SiN multilayers after He irradiation - Uglov V. V. Vladimir Vasilievich; Abadias G.; Zlotski S. V.; Kvasov N. T. Nikolay Trafimovich; Saladukhin I. A.; Malashevih А. А. (2018, 2018)
Title screen